2008
DOI: 10.1038/jid.2008.71
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Autoimmune Responses to the Squamous Cell Carcinoma Antigen Protein Family in Psoriasis

Abstract: Substantial evidence indicates that psoriasis is a T-lymphocyte-mediated autoimmune disease. However, longstanding data also indicate IgG and complement deposition in upper epidermis of psoriasis plaques. This led us to propose that autoantigen-autoantibody interactions in the skin may also be of pathogenic importance. Here, we have confirmed the presence of IgG in upper lesional epidermis and used high-resolution two-dimensional immunoblotting of extracts from this tissue, and laser desorption mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 33 publications
1
20
0
5
Order By: Relevance
“…Our results suggest that serum CA 125 levels differ according to the type of effusion, with significantly higher concentrations in patients with ascites and different cut points may be used according to the effusion type. However, other tumor markers, such as SCC, show indistinguishable concentrations in some conditions such as renal failure or dermatological disorders and patients with these pathologies may be excluded [36,37]. Using these criteria, our specificity was individually higher than 98.9%, and using all tumor markers, it was also high-97.5%.…”
Section: Discussionmentioning
confidence: 79%
“…Our results suggest that serum CA 125 levels differ according to the type of effusion, with significantly higher concentrations in patients with ascites and different cut points may be used according to the effusion type. However, other tumor markers, such as SCC, show indistinguishable concentrations in some conditions such as renal failure or dermatological disorders and patients with these pathologies may be excluded [36,37]. Using these criteria, our specificity was individually higher than 98.9%, and using all tumor markers, it was also high-97.5%.…”
Section: Discussionmentioning
confidence: 79%
“…Firstly, although poorly understood, the skin can be infiltrated by a subset of B cells that connect innate with adaptive immunity [49]. Secondly, high-resolution two-dimensional immunoblotting assays revealed the presence of IgGs in the upper lesional epidermis of psoriasis plaques [50], also known to be positive for cutaneous HPV types [51]. It remains to be determined how the exact spatial-temporal mechanism(s) that finally protects against a papillomavirus infection in the skin operates.…”
Section: Discussionmentioning
confidence: 99%
“…Using a similar approach as we did, one study previously identified keratin 10-specific antibodies in sera of psoriasis patients by protein identification (El-Rachkidy et al ., 2008). Another recent study reported anti-keratin autoantibodies in patients with rheumatoid arthritis (Quismorio et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%